(3GdEfGHI Edi eYQaI GdeNJda ajge ef GdUMGHIs
(3ChdgG (B:s
(3hdh ehMhO efg bhdg (B: (3EHQGgje CHh ESeGYjd GdGTgdi Qhi MOjK ESMGb GdbQhi s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3bhdg (B: (3CHh GdedjM GdgPdi PcQg GHf efOI hGHh jYeQ ai LedI GdUMGHI hRYeG Gf QhGjJg Yf GHjg CUM s
(3GdfSNI HgG MhGTs
(3HgG WeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ , HgG NQe s
Keywords: (3GdJGQjNs